Community engagement and its implications for latrine Coverage and better hygiene and sanitation practices - UNICEF (UNICEF, 2017)
The International Decade for Action - Water for life 2005-2015 report states that sanitation remains a powerful indicator of the state of human development in any community. Access to sanitation bestows benefits at many levels. Cross-country studies show that the method of disposing of excreta is one of the strongest determinants of child survival: the transition from unimproved to improved sanitation reduces overall child mortality by about a third. Improved sanitation also brings advantages for public health, livelihoods and dignity-advantages that extend beyond households to entire communities.